2022
DOI: 10.33448/rsd-v11i10.31104
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive Neuromuscular Facilitation compared to usual resistance exercise therapy in individuals with knee osteoarthritis: a randomized clinical trial protocol

Abstract: Background/Aims: Knee osteoarthritis (KOA) is characterized by functional impairment in performing of daily life activities. Proprioceptive Neuromuscular Facilitation (PNF) is a treatment concept that recommends performing exercises within a context of functionality. To develop a protocol to evaluate the efficacy of (PNF) compared to conventional physiotherapy (CPT group) on pain reduction and improvement in physical functioning and quality of life in individuals with KOA. Methods: A protocol for a randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The results of Masekar et al (21) research, which compared the effect of PNF and Muscle Energy Technique (MET) on knee osteoarthritis, showed that PNF had a greater effect in improving pain, hamstring flexibility and range of motion in patients compared to MET. Also, the research results of Maia et al (22) demonstrated that PNF improved the physical performance and quality of life of people with KOA.…”
Section: Discussionmentioning
confidence: 95%
“…The results of Masekar et al (21) research, which compared the effect of PNF and Muscle Energy Technique (MET) on knee osteoarthritis, showed that PNF had a greater effect in improving pain, hamstring flexibility and range of motion in patients compared to MET. Also, the research results of Maia et al (22) demonstrated that PNF improved the physical performance and quality of life of people with KOA.…”
Section: Discussionmentioning
confidence: 95%